The Creativity Continuum and Some Organisational Implications - Clapp, Ph.D., Ray (ABAC ODI JOURNAL Vision. Action. Outcome, 2014)
The current managerial preoccupation with Innovation is addressed by way of a discussion that illustrates that creativity comes in a range of different styles from the Adaptive (incremental adjustments to the current ways of doing things) to the Innovative(new ways of doing things). Thus creativity in an organisational context to be successful needs diversity rather than a single style. The pursuit of a single style without diversity leads to a diminishing organisational performance Key Words: Problem-Solving, Creativity Continuum, Adaption, Innovation, Diversity, Organisational Performance.